Hubungan Antara Tayangan Drama Serial Korea Times dengan Minat Mahasiswa Menjadi Reporter - Verene Ysabell Lietania; Azka Muzakiah (Syntax Idea)
The world has been faced with changes in the digital era, especially in information communication, making it easier for humans to access various information. Whether in news, advertisements, radio broadcasts, film shows or dramas. Drama shows, especially dramas from Korea, are very popular among the public, seen from the birth of the Korean wave. The various themes raised made the storyline more diverse, one of which was the Times drama series, which picked up a reporter's story. So, the researchers are interested in researching the Times drama shows with the audience's interest in becoming reporters. This study aimed to determine the relationship between the Times drama program and the audience's interest in becoming a reporter. The theories used are the mass communication process, media exposure, and social learning. The quantitative correlational approach uses data collection techniques through questionnaires, observation, and literature. The questionnaire was distributed to 79 Faculty of Communication Unisba 2017 respondents and analyzed by statistical tests with the SPSS application. The results of this study obtained a correlation coefficient with the number 0,772. It can be interpreted that there is a strong relationship between drama shows and the variable of interest in being a reporter.